Development of Culture-Based Interactive Comic Media to Increase Students’ Mathematics Learning Motivation in Elementary Schools - Francisca, Yolla; Wahyudi , Wahyudi (Jurnal Gentala Pendidikan Dasar, 2025)
This study developed a culture-based interactive comic media to increase motivation to learn mathematics in elementary schools. This media was designed to introduce Javanese culture and create more active and creative learning. The method used in this study was Research and Development (R&D) using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection was conducted through observation, interviews, and questionnaires at SD Negeri Sumberejo 01 with fourth-grade students as subjects. The results showed that the developed culture-based interactive comic was rated valid by experts, with scores ranging from "Good" to "Very Good." The practicality score reached 86.85%, classified as "Very Practical." The t-test also indicated a significant improvement in students' learning outcomes. Therefore, the interactive comic is considered valid, practical, and effective in enhancing students' motivation and learning outcomes in mathematics, particularly in fraction material.